1999
DOI: 10.1073/pnas.96.18.10182
|View full text |Cite
|
Sign up to set email alerts
|

The tumor-suppressor activity of PTEN is regulated by its carboxyl-terminal region

Abstract: PTEN is a recently identified tumor suppressor inactivated in a variety of cancers such as glioblastoma and endometrial and prostate carcinoma. It contains an amino-terminal phosphatase domain and acts as a phosphatidylinositol 3,4,5-trisphosphate phosphatase antagonizing the activity of the phosphatidylinositol 3-OH kinase. PTEN also contains a carboxyl-terminal domain, and we addressed the role of this region that, analogous to the amino-terminal phosphatase domain, is the target of many mutations identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
260
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(270 citation statements)
references
References 28 publications
9
260
0
1
Order By: Relevance
“…In all cases there were 1 or 2 frameshift mutations that caused a premature stop codon before or at aminoacid 343, therefore presumably resulting in a protein with no functional activity. 52,53 Missense mutations were also present in all of these samples and none of them appeared to be polymorphisms as explained before. The presence of more that 2 mutations in the same gene in the same tumor specimen has been reported previously.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In all cases there were 1 or 2 frameshift mutations that caused a premature stop codon before or at aminoacid 343, therefore presumably resulting in a protein with no functional activity. 52,53 Missense mutations were also present in all of these samples and none of them appeared to be polymorphisms as explained before. The presence of more that 2 mutations in the same gene in the same tumor specimen has been reported previously.…”
Section: Discussionmentioning
confidence: 74%
“…52,53 As for the possible effect of the remaining 2 frameshift mutations, it is known that the last residues of the PTEN protein (PEST domains: residues 350-375 and 379-396, and PDZ domain: residues 400-403) are important for protein stability and for its interaction with other proteins, so they may also be functional. 54 Seventeen different types of variants constituted the 30 missense mutations.…”
Section: Pten Gene Mutationsmentioning
confidence: 99%
“…Aberrant PTEN signaling is associated with metastasis and poor prognosis in breast and other cancers (Saal et al, 2007). Genetic alterations of the PTEN gene range from point mutations (encoding mostly unstable and/or catalytically inactive proteins) to large chromosomal deletions Steck et al, 1997;Georgescu et al, 1999Georgescu et al, , 2000. Among these mutations are structural rearrangements within the PTEN gene (intragenic inversions, insertions, deletions and duplications known as gross PTEN mutations) that occur in BRCA1-associated basal-like breast cancer (Saal et al, 2008).…”
Section: Perturbations Of Pten Signaling In Cancermentioning
confidence: 99%
“…Although several randomized trials have confirmed a better overall and complete response rate for the combination of fludarabine and cyclophosphamide compared with fludarabine alone, no differences in the OS were observed. 7,8 In the British study, the oral formulation of fludarabine was introduced in both fludarabine arms when the drug became available, and differences in response rates between the two routes of administration did not appear significant. Oral fludarabine is an effective treatment for patients with previously untreated B-CLL, with less health resource utilization compared with IV administration.…”
mentioning
confidence: 99%